DOMAIN NAME - Gunawan Widjaja; Athalia Christine L; Anindita Widyapradnya; Lidya Cristy S (Cross-border, 2018)
Domains are very helpful because the chances of fraud happening are very small. This can be seen in the registration method which can be said to be quite strict. To register a domain, general requirements are needed, which include not violating patent rights and being required to report a clear identity legally.